On Stream Analysis at Brenda Mines Limited Ten Years Experience with ARL's PCXQ X ray Analyser - Derek Perkins (Canadian Institute of Mining, Metallurgy and Petroleum, 1989)
"Brenda Mines Ltd. operates an open pit copper and molybdenum mine located in south central British Columbia. The main economic mineralization is chalcopyrite and molybdenite. Pyrite, galena and sphalerite are also present in varying quantities. The mineralization is present in small veins and fractures in a porphyritic quartz diorite host rock.The mill processes approximately 30,000 tonnes of ore daily. The ore is crushed in three stages and then ground in conventional rod mill - ball mill circuits with cyclone classification. The cyclone overflow is fed to the bulk flotation circuit as a pulp with a density of 50% solids. The particle size distribution is approximately 35% plus 65 mesh. Bulk rougher and cleaning flotation produce a concentrate grading approximately 20% copper and 4% molybdenum. This concentrate is fed to the separation circuit, where the copper is depressed with sodium hydrosulphide and the molybdenum is floated. These products are further ground and then upgraded by column flotation. The molybdenum concentrate is pumped to the leach plant to reduce concentration of lead and copper. It is then washed, filtered, dried and packed for shipment to Europe. The copper concentrate is filtered, dried and subsequently shipped to Japan.Prior to November 1977, the mill flotation control was carried out by the assay laboratory using a Philips PW 1540 sequential x-ray spectrograph. The assay set consisted of twelve samples, analysed on a two hourly basis for copper, molybdenum, lead, iron and silica.In order to provide elemental composition information on a much shorter sampling interval and to produce speedier control analysis for automating process control, an Applied Research Laboratories PCXQ on stream analyser was purchased. The installation of this analyser, reduced the turnaround time of the control analyses from (2) hours to (20) minutes. At Brenda, the following assays are used in the mill control strategies."